Влаштування дітей-сиріт та дітей, позбавлених батьківського піклування, як реалізація принципу державної охорони сім’ї - Токарчук, Людмила Михайлівна; Токарчук, Людмила Михайловна; Tokarchuk, Liudmila M. (My University, 2021)
Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.03 – цивільне право і цивільний процес; сімейне право; міжнародне приватне право. – Національний університет «Одеська юридична академія», Одеса, 2021. Дисертація є першим у вітчизняній науці спеціальним комплексним дослідженням правових проблем влаштування дітей-сиріт та дітей, позбавлених батьківського піклування, як реалізації принципу державної охорони сім’ї. У процесі здійснення дослідження у роботі розроблено і обґрунтовано концепцію полісистемної турботи щодо дітей-сиріт та дітей, позбавлених батьківського піклування, як діяльності держави, громадянського суспільства (недержавних і комерційних інституцій), окремих фізичних осіб із охорони і захисту прав та інтересів дітей, сприяння їхньому добробуту, можливості реалізації свого життєвого і творчого потенціалу, що ґрунтується на нормах міжнародного та національного права. Визначено основні засади концепції, окреслено коло питань, які мають стати стратегічними напрямами вдосконалення законодавства, а також основні напрями реалізації державної політики в зазначеній сфері. До основних висновків і пропозицій, сформульованих у роботі, належать такі: щодо визначення понять «форми влаштування дітей-сиріт та дітей, позбавлених батьківського піклування», «усиновлення», «опіка та піклування» та їх змісту; висновки щодо правової природи патронату та місця норм про патронат у законодавстві; відносно забезпечення найкращих інтересів дитини при вирішенні питання про можливість спілкування між колишніми підопічними і прийомними батьками; щодо збереження інтернатних закладів; щодо унормування процедури усиновлення у закордонних дипломатичних установах України. Обґрунтовано пропозицію щодо необхідності невідкладного приєднання України до Конвенції про захист дітей та співробітництво в галузі міждержавного усиновлення від 29 травня 1993 р. і реформування у зв’язку з цим законодавства, що врегульовує відносини з усиновлення. Сформульовано низку пропозицій щодо удосконалення норм СК України, інших нормативно-правових актів, що врегульовують відносини з охорони прав та інтересів дітей, влаштування дітей-сиріт та дітей, позбавлених батьківського піклування.

Диссертация на соискание научной степени доктора юридических наук по специальности 12.00.03 – гражданское право и гражданский процесс; семейное право; международное частное право. – Национальный университет «Одесская юридическая академия», Одесса, 2021. Диссертация является первым в отечественной науке специальным комплексным исследованием правовых проблем устройства детей-сирот и детей, оставшихся без попечения родителей, как реализации принципа государственной охраны семьи. В процессе проведения исследования в работе разработана и обоснована концепция полисистемной заботы о детях-сиротах и детях, оставшихся без родительского попечения работы, как деятельности государства, гражданского общества (негосударственных и коммерческих институтов), отдельных физических лиц по охране и защите прав и интересов детей, содействию их благосостоянию, возможности реализации своего жизненного и творческого потенциала, основанных на нормах международного и национального права. Определены основные принципы концепции, очерчен круг вопросов, которые должны стать стратегическими направлениями совершенствования законодательства, а также основные направления реализации государственной политики в указанной сфере. К основным выводам и предложениям, сформулированным в работе, относятся: определение понятий «формы устройства детей-сирот и детей, лишенных родительской опеки», «усыновление», «опека и попечительство» и их содержание; выводы относительно правовой природы патроната и места норм о патронате в законодательстве; суждения об обеспечении наилучших интересов ребенка при решении вопроса о возможности общения между бывшими подопечными и приемными родителями; предложения по сохранению интернатных учреждений; рекомендации по урегулированию процедуры усыновления в зарубежных дипломатических учреждениях Украины, и др. Обосновано предложение о необходимости немедленного присоединения Украины к Конвенции о защите детей и сотрудничестве в области межгосударственного усыновления от 29 мая 1993 г. и реформирования в связи с этим законодательства, регулирующего отношения по усыновлению. Сформулирован ряд предложений по совершенствованию норм СК Украины, других нормативно-правовых актов, регулирующих отношения по охране прав и интересов детей, устройства детей-сирот и детей, оставшихся без попечения родителей.

Dissertation for the degree of Doctor of Law in the specialty 12.00.03 – Civil Law and Civil Process; Family Law; International Private Law. – National University “Odesa Law Academy”. Odesa, 2021. The dissertation is the first in the domestic science of comprehensive study of the legal problems of the arrangement for orphans and children deprived of parental care, as the implementation of the principle of State family’s protection. Every child deserves a happy childhood in all its manifestations, the environment with the love and care of the family, the protection of the state, society and community, the opportunity to grow and fully develop. In Ukraine, the vector of State social policy on children and society’s perception of ways and means of protecting orphans and children deprived of parental care has changed over the last thirty years. The approval by order of the Cabinet of Ministers of Ukraine dated 09.08.2017 No. 526-r of the National Strategy for the Reform of the System of Institutional Care and Upbringing of Children for 2017–2026 and the action plan for the implementation of its first stage updated the issue of using family forms of arrangement for orphans and children deprived of parental care. In the process of the research, the author developed and substantiated the concept of polysystem care for orphans and children deprived of parental care, as the State activity, civil society (non-State and commercial institutions), individuals to protect and defend the rights and interests of children, to promote their well-being, and to realize their life and creative potential, based on the norms of international and national law. The basic principles of the concept are defined, the range of issues that should become strategic directions for improving legislation, as well as the main directions for implementing state policy are outlined. The main conclusions and offers of the work are: concerning definition of a concept “a form of arrangement for orphans and children deprived of parental care”, “adoption”, “custody and guardianship” and their contents; conclusions regarding the legal nature of the patronage and the place of the rules on patronage in the legislation; concerning the provision of the best interests of the child when considering the possibility of communication between former wards and foster parents; the preservation of residential institutions; regarding the rationalization of adoption procedures in foreign diplomatic institutions of Ukraine, etc. The definition of adoption as a form of arrangement for orphans and children deprived of parental care has been formulated. Adoption is the acceptance by the adoptive parent (s) of a child into their family and is carried out by a court decision, resulting in rights and obligations similar to those between parents and children and their relatives, on the one hand, and between the adoptive parent and descendants. It is proposed to understand guardianship (custody) as a form of arranging for orphan or child deprived of parental care into a family in order to ensure and protect his personal non-property and property rights and interests. It is proved that relationships are often formed between foster parents, foster parents and wards, which in fact can be considered family, and not simply to provide services for the maintenance and upbringing of the child. In the case of such relations, their participants have the right to communicate, meet even after the termination of the support agreement. In the event of a dispute about the right of communication between foster parents, foster parents and biological parents of former wards, the court should be based on the principles of the best interests of the child, as well as take into account the interests of actual educators and parents. On the basis of a systematic analysis of the norms of the current legislation on patronage, it is concluded that patronage is not a form of arrangement for orphans and children deprived of parental care, but has signs of social service. Contradictions in the rules governing the relationship of the patronage make their understanding unfaithful, lead to disputes and abuse of orphans and children deprived of parental care. Given the purpose of establishing patronage, taking into account the ambiguity of the term “patronage” in the legislation, as well as the fact that the Family Code of Ukraine regulates family relations, and not social security relations, the provisions of chapter 20 of section IV should be revised, its norms should receive clear forms on the purpose, grounds and rules for establishing patronage over children. There is justified the proposition to accede immediately to the Convention on Protection of Children and Cooperation in Respect of Intercountry Adoption of May, 29, 1993 and to reform in this regard the legislation, which regulates the adoption relationship. There are formulated the proposals to improve the norms of the Family Code of Ukraine, other legal acts, that regulate relations on protection of the rights and interests of children, the arrangement for orphans and children deprived of parental care.
дис. ... докт. юрид. наук: 12.00.03
Токарчук Л.М. Влаштування дітей-сиріт та дітей, позбавлених батьківського піклування, як реалізація принципу державної охорони сім’ї: дис. ... докт. юрид. наук: 12.00.03 / Токарчук Людмила Михайлівна. Одеса, 2021. 512 с.
Keywords: сімейна політика держави; деінституціалізація; інституційний догляд; інтернатні заклади; прийомні батьки; батьки-вихователі; патронат; прийомна сім’я; дитячий будинок сімейного типу; піклування; опіка; усиновлення; дитина, позбавлена батьківського піклування; дитина-сирота; ребенок-сирота; государственная семейная политика; ребенок, оставшийся без попечения родителей; деинституциализация; институциональный уход; интернаты; приемные родители; родители-воспитатели; патронат; приёмная семья; детский дом семейного типа; попечительство; опека; усыновление; family policy of the State; deinstitutionalization; institutional care; boarding schools; adoptive parents; mentors; patronage; family-type orphanage; guardianship; custody; adoption; child deprived of parental care; orphan child